Analisis Kekuatan Tarik Komposit Laminat Jute Berdasarkan Pola Kerusakan Kolom Silinder Metode Split Tensile Test - Al Rasyid, Al Rasyid; Jusuf Zulfikar, Achmad; Iswandi, Iswandi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
The purpose of this study is to obtain the damage pattern of cylindrical column concrete specimens (BKS) reinforced with laminate jute composite (KLJ) based on the results of the Split Tensile Test, to determine the phenomenon of applying laminated jute composite reinforcement to cylindrical column concrete on the percentage of crack patterns ( PPR) specimens, and analyze the comparison between split tensile strength (KTB) and PPR. The test specimens were printed based on the ASTM C496 test standard using the Vacuum Bagging method. Specimen variations consist of 1 to 4 layers of KLJ and one variation without KLJ sheath as a control specimen. The split tensile test used the UTM test tool with each variation being carried out with 3 repetitions. PPR observations and calculations were carried out with the help of Adobe Photoshop software. The results of the study show that the greater the KTB value, the greater the PPR that occurs. The increase in PPR in each KTB is reported in this article.